Investigation into the electrochemical behaviour of silver in alkaline solution and the influence of Au-decoration using operando Raman spectroscopy. Issue 14 (26th February 2020) - Luo, Haowei; Ji, Xu; Cheng, Shuang
Abstract : Apart from the traditional charge storage mechanism demonstrated in CV, a two-electron process of Ag to AgO is revealed in GCD. Abstract : To explore the basic chemistry in the electrochemical environment, the electrochemical behavior of Ag and the influence of Au decoration is investigated with cyclic voltammetry (CV), galvanostatic charge–discharge (GCD) and operando Raman measurements in a 1 M KOH solution. During the anodic CV sweep, Ag is oxidized to Ag2 O in the first step through a one-electron process, and then, AgO in the second step through another one-electron process. Meanwhile, some AgO is formed at a relatively low potential under the irradiation of visible lights (photoelectrochemical oxidation). In the GCD mode, it is found that apart from the two one-electron processes, part of the Ag is oxidized to AgO directly through a two-electron process in the second oxidation step, implying slightly different activities of these reactions in the CV and GCD mode. During cathodic CV sweep and galvanostatic discharge, opposite reactions take place respectively. The coulombic efficiency is calculated to be only ∼82% from the CV cycle at 5 mV s −1 due to the formation of silver hydroxyl species (oxidation state) in a low potential range. For the Au decorated Ag, Raman signals from these species disappeared and the coulombic efficiency is enhanced to 95%, indicating an obvious improvement in reversibility.